Secagem em camada de espuma da babosa para utilização em formulação cosmética - Bonfim, Karina Soares do (2019)
The Aloe vera, popularly known as Babosa, is a plant of the family Liliaceae and the genus Aloe. Drying is a way to preserve nutrients, conserve food, and increase shelf life. Among the existing types can be highlighted the foam-mat drying as it is a simple alternative and low cost. The objective of this research was to evaluate the foam-mat drying of the gel of babosa to obtain its powder form and to test its application in shampoo and conditioner formulations. The methodology of the full factorial experimental design of 2³ + 3 central points was used, with the input variables: foaming concentration, agitation time and drying temperature. Output variables: final moisture on dry basis and final drying time. The foaming agent used was the powder of the juá. The physical characterization of the foam was performed through the analysis of density, stability, air incorporation capacity and percentage of expansion. The data of the drying kinetics obtained were adjusted to nonlinear mathematical models. For the physical-chemical characterization of the powder used in the cosmetic formulations, the ash, moisture, proteins and lipids analyzes were performed. Formulations of shampoo and conditioner containing the powder at the concentrations of 0.5%, 1.5% and 3.0% were tested. And a formulation without powder called control. In order to evaluate the formulation, the accelerated stability study and the wicks test were carried out, which involves the penteability and the brightness analysis. As well as the sensorial analysis of the formulations through the test of acceptance and attitude of purchase using the hedonic scale of 9 points and the structured scale, respectively. The foam-mat drying proved to be efficient for obtaining the powder. The most stable foam was obtained for conditions of 5% foaming, 6 min stirring and 50°C. By the statistical analysis it was observed that the air incorporation capacity and the percentage of expansion increased with the increase of the studied variables. The opposite occurred for density. The input variables of the experimental design of the drying were not statistically significant for the responses. The drying kinetics obtained had good adjustments for the Page and Newton models. The powder chosen for the formulations was obtained at the maximum levels of the planning, whose physical-chemical characterization of this powder showed a higher concentration of ash, lipids and proteins after drying. Formulations of shampoo and conditioner containing the powder of babosa were obtained and the accelerated stability analysis showed the instability of the shampoo formulation. A new formulation was made, with the highest penteability observed for the 3% concentration and the increase of the brightness to 0.5%. The formulation of the shampoo at 3% concentration and the 0.5% conditioner were the best evaluated in the sensorial analysis. Lastly, the use of aloe vera powder is recommended as an unprecedented cosmetic asset with excellent hair treatment response.